HIDDEN CURRICULUM SEBAGAI MEDIA PEMBENTUKAN AKHLAK: STUDI KASUS PEMBIASAAN RELIGIUS DI PERKULIAHAN PBSI UIN JAKARTA - Salsabila Putri Aulia, Michelle Taj Ghina, Niha Nurazizah (JURNAL PENDIDIKAN IPS, 2026)
This study examines the role of the hidden curriculum as a medium for shaping students’ moral character through religious habituation practices implemented in the PBSI (Indonesian Language and Literature Education) program at UIN Jakarta. The hidden curriculum encompasses values, habits, and ethical norms that are not written in the formal curriculum but significantly influence character development. Using a qualitative literature-based approach, this study analyzes scholarly works related to hidden curriculum implementation and religious practices in higher education. Data were analyzed descriptively to explore habituation patterns such as opening and closing prayers, polite behavior, lecturer role-modelling, and students’ reflection activities on commendable and reprehensible acts. The findings show that religious habituation effectively internalizes moral values, enhances discipline, fosters responsibility, and strengthens academic integrity among students. The study concludes that synergy between the formal curriculum and hidden curriculum must be reinforced to create an academic environment that supports the development of morally upright and religiously grounded students.